1995
DOI: 10.1021/bi00005a035
|View full text |Cite
|
Sign up to set email alerts
|

Gin Invertase of Bacteriophage .mu. is a Dimer in Solution, with the Domain for Dimerization in the N-Terminal Part of the Protein

Abstract: The Gin protein of bacteriophage Mu mediates recombination between two inverted repeat sequences. Gin binds as a dimer to each of these recombination sites. We show that Gin is a dimer in solution also, and that the dimerization is probably stabilized by hydrophobic interactions between the subunits. The subunits of the dimer could efficiently be cross-linked with the 4-A cross-linker diepoxybutane. Spontaneous oxidation of Cys(24) and/or Cys(27) also resulted in intersubunit cross-linking. One or both cystein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

1995
1995
2007
2007

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
2
1
Order By: Relevance
“…The data presented in this paper demonstrate that the functional dimer interface of the Hin recombinase is within the helix-E region. This conclusion differs from a recent report on the related DNA invertase, Gin, in which it was concluded that the solution dimer interface is on the opposite end of the monomer [29]. We, along with Lim [24], find that the efficient formation of disulfide bonds in Hin, both in solution, which generates covalentlylinked dimers that are fully active in binding to hix, and when bound to hix DNA, occurs between residues within the amino-terminal end of the presumed E-helix of Hin.…”
Section: Structure Of the Hin Dimercontrasting
confidence: 99%
“…The data presented in this paper demonstrate that the functional dimer interface of the Hin recombinase is within the helix-E region. This conclusion differs from a recent report on the related DNA invertase, Gin, in which it was concluded that the solution dimer interface is on the opposite end of the monomer [29]. We, along with Lim [24], find that the efficient formation of disulfide bonds in Hin, both in solution, which generates covalentlylinked dimers that are fully active in binding to hix, and when bound to hix DNA, occurs between residues within the amino-terminal end of the presumed E-helix of Hin.…”
Section: Structure Of the Hin Dimercontrasting
confidence: 99%
“…8 demonstrates that increasing concentrations of FinB-MBP gave rise initially to a single protein/DNA complex (complex 1) that was eventually converted to a slower migrating complex (complex 2). Based on the documented attributes of the serine family of sitespecific recombinases to either form dimers in solution or bind cooperatively to DNA as dimers (Spaeny-Dekking et al, 1995;Blake et al, 1995), one simple interpretation of the binding pattern (Fig. 8) is that a dimer of FinB-MBP was bound at either fix1L or fix1R to generate complex 1 and that at higher protein concentrations both recombination sites were occupied to give rise to complex 2.…”
Section: Resultsmentioning
confidence: 99%
“…Our tentative conclusion is that, in our assays, Tn3 resolvase is mainly monomeric in solution, but y resolvase is mainly dimeric; however, the end result of binding is the same (site II occupied by a resolvase dimer). Gin invertase, which is a member of the resolvase family of recombinases, may also be partly monomeric in solution [33,34].…”
Section: Monomers and Dimersmentioning
confidence: 99%